Teacher agency in perceiving affordances and constraints of videoconferencing technology: Teaching primary school students online. (August 2022) - Jeon, Jaeho; Lee, Seongyong; Choe, Hohsung
Abstract: Despite some evidence in the literature on the evolving and emergent nature of technological affordances, the role of teacher agency in noticing, selecting, and utilizing those affordances in the context of L2 online teaching has not been fully explored. In addition, while previous research on technological affordances has focused on adult students, little has been known about how teacher agency is manifested in relation to ICT affordances when teaching young learners in large-sized L2 classes. Thus the present study, adopting the ecological perspective on teacher agency and affordance, aims to investigate how primary school English teachers enacted and exerted their teacher agency in response to pedagogical challenges by exploring and exploiting the pedagogical affordances of a synchronous videoconferencing tool. Qualitative data collected from semi-structured interviews with 10 English teachers in South Korea reflected that their teacher agency guided by their pedagogical beliefs contributed to evolving ICT affordances for L2 online teaching, responding to institutional expectations and technological constraints. The findings also showed that the characteristics of young English learners mediated their agency enactment in ways that teachers noticed technology affordances and constraints while addressing pedagogical issues regarding teaching young learners. Academic implications from the perspective of teacher agency are discussed.